ANALISIS USAHATANI SAYURAN SELADA MENGGUNAKAN HIDROPONIK SEDERHANA PADA LAHAN PEKARANGAN - Amalia, Anugerah Fitri; Fitri, Annisa; Dalapati, A.; Fahmi, Femmi Nor (Universitas Galuh Ciamis, 2020)
The increase of population caused many agricultural land converted into settlements, so the challenge of fulfilling food from the agricultural sector is increasing. One of the efforts to optimize the fulfillment of food needs from increasingly narrow land is to use the plots of land with hydroponic system plantations. This study is aimed to analyze the advantages of hydroponic organic lettuce in the DFT (Deep Flow Technique) system in the plots, break-even points of hydroponic farming, and R / C ratio of hydroponic vegetable farming. This research was carried out in March to April 2019. in the yard of the Sidondo Agricultural Technology Research and Assessment (IP2TP) office located in Sidondo III Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi Province. This research using cost and income analysis, break even point, and R / C ratio. The results of the study through break-even analysis or Break Even Point (BEP) analysis viewed from two sides: in terms of total production / BEP (Q) and in terms of selling price / BEP (Rp), a DFT BEP (Q) of 32.5 is obtained kg and Rp. 18,581 on BEP. It's obtained 2.15 on R / C Ratio Analysis in farming. Hydroponic farming in the backyard is profitable.